Biofertilizers for Sustainable Agricultural Practice in Crop Production: A Review - Samanta, Kousik; Islam, Aminul; Banik, Madhurima; Koley, Shankha (AGRIVITA Journal of Agricultural Science, 2025)
By 2050, a projected global population of 9.7 billion will exacerbate the existing resource scarcity, demanding innovative solutions for sustainable food production. While synthetic fertilizers have boosted yields, their environmental impact—including soil and water contamination, greenhouse gas emissions, and declining response rates—is undeniable. Organic farming and the utilization of biofertilizers offer a compelling alternative. These naturally occurring microorganisms, including nitrogen-fixing bacteria and phosphorus-solubilizing bacteria, enhance soil fertility, boost crop yields, and mitigate the negative consequences of chemical fertilizers. While challenges remain regarding production, distribution, and widespread farmer adoption, the growing global demand for sustainable agriculture, coupled with ongoing research into biofertilizer optimization, paints an optimistic picture for the future of this eco-friendly technology. Indeed, the shift towards biofertilizers represents not just a solution to a pressing problem but a crucial step towards a healthier planet and more secure food supply. The findings suggest that excessive use of chemical fertilizers negatively affect agricultural ecosystems. Besides this, the use of biofertilizers offers a natural sustainable alternative solution to address the imbalance of soil nutrients.